Allelic variants of ADH, ALDH and the five factor model of personality in alcohol dependence syndrome - Salujha, SK; Chaudhury, S; Menon, PK; Srivastava, K; Gupta, A (Industrial psychiatry journal, 2014)
The etiology of alcohol dependence is a complex interplay of biopsychosocial factors. The genes for alcohol-metabolizing enzymes: Alcohol dehydrogenase (ADH2 and ADH3) and aldehyde dehydrogenase (ALDH2) exhibit functional polymorphisms. Vulnerability of alcohol dependence may also be in part due to heritable personality traits. To determine whether any association exists between polymorphisms of ADH2, ADH3 and ALDH2 and alcohol dependence syndrome in a group of Asian Indians. In addition, the personality of these patients was assessed to identify traits predisposing to alcoholism. In this study, 100 consecutive males with alcohol dependence syndrome attending the psychiatric outpatient department of a tertiary care service hospital and an equal number of matched healthy controls were included with their consent. Blood samples of all the study cases and controls were collected and genotyped for the ADH2, ADH3 and ALDH2 loci. Personality was evaluated using the neuroticism, extraversion, openness (NEO) personality inventory and sensation seeking scale. Allele frequencies of ADH2*2 (0.50), ADH3*1 (0.67) and ALSH2*2 (0.09) were significantly low in the alcohol dependent subjects. Personality traits of NEO personality inventory and sensation seeking were significantly higher when compared to controls. The functional polymorphisms of genes coding for alcohol metabolizing enzymes and personality traits of NEO and sensation seeking may affect the propensity to develop dependence.